First high resolution analysis of the 2ν1, 2ν3, and ν1 + ν3 bands of S18O2. (December 2016) - Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Zamotaeva, V.A.; Sklyarova, E.A.; Sydow, C.; Maul, C.; Bauerecker, S.
Abstract: We report the results of a highly accurate, (1–3)×10 −4  cm −1, ro-vibrational analysis of the S 18 O2 molecule in the spectral region of 2100–2700 cm −1 . More than 2910, 2130, and 1390 transitions belonging to the 2 ν 1, ν 1 + ν 3, and 2 ν 3 bands were assigned for the first time with the values of quantum numbers J max . / K a max . equal to 67/26, 81/25 and 53/16, respectively. The weighted fit of experimentally assigned transitions was made with the Hamiltonian model which takes into account Coriolis resonance interactions between the vibrational states ( v 1 v 2 v 3 ) and ( v 1 ∓ 1 v 2 v 3 ± 1 ) and Fermi interactions between the states ( v 1 v 2 v 3 ) and ( v 1 ∓ 1 v 2 ± 2 v 3 ) . To make the ro-vibrational analysis physically more suitable, the initial values of main spectroscopic parameters have been estimated theoretically. Finally, the set of 43 spectroscopic parameters obtained from the fit reproduces values of 2384 initial "experimental" ro-vibrational energy levels (more than 6430 transitions assigned in the experimental spectra) with the rms = 1.74 × 10 − 4 cm − 1 . Abstract : Highlights: High resolution analysis of 32 S 18 O2 FTIR spectra. Resonance interactions. Determination of spectroscopic parameters.